Tutorial on Applied Study Designs in Medical Research - Bahariniya; Farzan Madadizadeh; Elham Khaledi; Mehrnoosh Qomi (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: One of the main pillars of the study is the correct choice of study design. This study aimed to give an overview of different type of study designs in medical research. Methods: In this tutorial study, all applied research designs in terms of quantitative and qualitative study were reviewed. Accordingly, terms related to "Research Designs" were searched in the online databases such as Google Scholar, PubMed, Web of Science and Scopus. Results: Based on the findings of the present study, the types of studies are generally divided into two groups: quantitative studies and qualitative studies. Quantitative studies are divided into two categories: primary and secondary studies. Preliminary studies include observational and non-observational studies. Observational studies are divided into two categories: descriptive and analytical studies. Descriptive studies include case reports, cross-sectional studies, cross-sectional correlational studies and ecological studies, and analytical studies include retrospective and group studies. Non-observational studies also include laboratory studies, clinical trials, field trials, and community trials. Conclusion: With a good understanding of the types of studies, it is easy to decide which type of study is appropriate for the research. Choosing proper study design can reduce the costs of the executive process, increase the accuracy, quality of research and give more reliable results. Corrigendum at https://jhr.ssu.ac.ir/article-1-962-en.html